Tanggung Jawab Direksi dalam Meningkatkan Citra Bank (Suatu Telaah Yuridis Normatif) - Sriayu Indah Puspita (Universitas Batanghari Jambi, 2021)
At this time the banking world has a very important function in the Indonesian economy. Banking is an institution that functions to collect and distribute public funds. For this reason, in order to maintain public trust in the bank, the government continues to try to protect or protect the public from irresponsible persons who can damage public trust in the bank. The issue of civil liability for negligence or carelessness that occurs in a bank can be related to the management of the bank. In order to increase the function of common awareness towards banking institutions, regulations regarding bank secrecy which have been very secretive must be revised immediately. The bank secrecy in question is one of the elements that every bank needs to have as an institution of public trust. Banking practices that violate the laws and regulations in the banking sector as long as these regulations are considered a weakness that can harm their interests, even the owner or management of the bank uses the existing regulatory loopholes so that in the end the bank is in an unhealthy condition. For that we need to know and understand how the bank can improve its image and the role of the board of directors in overcoming the problems faced and how to overcome these problems. The Board of Directors has an important role in the management of the bank, the board of directors is also required to regulate the bank according to its authority and responsibility as stipulated in the articles of association and the provisions of the applicable regulations. The image of the bank is built through communication programs and combined with customer experiences interacting with the bank.